Jerzy Ronard Bujański – powojenne pół sezonu w Starym Teatrze - Kornaś , Tadeusz (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
Jerzy Ronard Bujański was the first director of the Old Theatre after the Second World War (from the end of January to August 1945). The article presents turbulent beginnings of this management (the war was still in progress). Besides, the first premiere of the Old Theatre - Mąż doskonały by Jerzy Zawieyski - directed by Bujański, stage design by Andrzej Pronaszko. This performance referred to the character of Job from the Old Testament and was related to the Warsaw Uprising context. This show was one of the most important artistic events of the first season after the war. Next to the Old Theatre, Bujański established the Studio, which educated about one hundred people. The teachers included: Juliusz Osterwa and Tadeusz Kantor, while the students were, for example Tadeusz Łomnicki, Halina Mikołajska, Andrzej Hiolski, Kazimierz Mikulski and Jerzy Nowosielski. In August 1945, Jerzy Ronard Bujański was dismissed as a result of a conflict with the city authorities. However, during the time of his management, the theatre gained a high artistic position.